KE-HUJJAH-AN HADIS DHA’IF DI KALANGAN AHLI - Ali Sati (Institut agama islam negeri Padangsidimpuan, 2018)
As the second of the Islamic law’s resource, there is a stipulation that be must be owned by the Sunna, so that can be accepted, that’s the genuine quality. By this way, appeared some requestions and notions from the omnicients (al-´ulama). For example; how the demontration of the feeble Sunna. The feeble or weak Sunna, it means as the every Sunna that not be gathering the accepted atributs in it.